Magnetorheological Dampers in Landing Gears: Dynamic Analysis Focused on Shock Absorption and Vibration Comfort - de Abreu, Felipe Lima; Filipus, Murilo Cesar; Bueno, Douglas D. [UNESP]; Santos, Rodrigo B. (Springer Nature, 2025)
This chapter investigates the use of Magnetorheological (MR) dampers in aircraft landing gear, aiming to improve safety, efficiency, and comfort during the landing. MR dampers can adjust the damping force in real time, adapting its behavior to specific needs during this critical phase of the flight. The study considers the Spencer dynamic model, which includes non-linear characteristics, such as that the hysteretic effect, and the decrease in the damping force if the velocity approaches zero. The work introduces force decomposition to the actuator into hydraulic, pneumatic, and active components. The landing gear system is modeled with two degrees of freedom, taking into account the vertical oscillations. The analysis is conducted by numerical simulations using the fourth-order Runge–Kutta integrator method. The results are evaluated in terms of shock absorption efficiency and vibration comfort. The results obtained demonstrate the potential of the technologies based on MR dampers to improve flight safety and efficiency. Furthermore, these technologies have potential industrial applications to make landings more comfortable for passengers.
Keywords: Dynamics analysis; Landing gear; MR damper; Vibration comfort